Pace and variability in the badminton jump smash and the tennis serve - Miller, R. N.; Dillon, R. N. (2016)
Full-body three-dimensional kinematic characteristics were determined for the badminton jump smash and the tennis serve in order to investigate contributions to pace and variability. Kinematic (400 Hz) data were collected for a group of badminton and tennis players, using an 18 camera Vicon Motion Analysis System. Each participant performed 24 jump smashes or tennis serves. The best trials - maximal velocity with minimal marker loss - were analysed for each participant using a 18 segment rigid body model customised for each participant using subject-specific segmental properties. Parameters were calculated describing elements of the badminton jump smash and tennis serve technique as well as variability. The effect of these technique parameters on: speed were addressed using stepwise linear regression and on variability using one-way ANOVA. The results suggest that the fastest badminton players had a smaller elbow extension angle at the end of retraction, a larger wrist extension angle at shuttle contact, and a larger time between preparation and shuttle contact; that accounted for 84% of variation in shuttle speed. The results also showed that variability in the badminton smash was caused by differences in body placement, shuttle location on the racket at impact and movement timings. In the tennis serve, linear regressions showed that there were no variables significant to speed when players hit to the right and left centre court lines. When players hit in the advantage court trunk rotation at the racket lowest point key instant could explain 35.2% of the variation in speed, and when hitting towards the deuce court timing from the end of retraction to ball contact explained 33.6% of ball speed. The results show that there are differences in technique between the badminton jump smash and the tennis serves especially in the first half of the sporting actions.